A new species of the Yelicones Cameron (Hymenoptera: Braconidae: Rogadinae) from Thailand - Buntika Areekul Butcher (Magnolia Press, 2014)
Yelicones samaesanensis Butcher, new species, is described and illustrated based on a female and male specimens collected at light trap in Chonburi province, Thailand. This wasp is the tenth species of Yelicones described from the East Palaearctic and Oriental regions. Y. samaesanensis appears closest to Y. contractus Papp from Vietnam and India. A key is included to differentiate Y. samaesanensis from the similar species.